The World Of Hannah More - Demers, Patricia, 1946- (Book collections on Project MUSE., 1996)
History has not been kind to Hannah More. This once lionized writer and activist -- the most influential female philanthropist of her day -- is now considered by many to be the embodiment of pious morality and reactionary anti-feminism. Largely because of her belief in separate spheres for men and women, More has been vilified by modern-day feminists. The first biography to examine the complete range of her life and work, The World of Hannah More depicts the author as a forceful voice in her own day and one who, from the point of view of plain justice, today deserves a more nuanced treatment.